Factors that Influence the Synergy between Development and IT Operations in a DevOps Environment - Dinner, Arther (Department of Information Systems, 2021)
Software development processes have been associated with severe conflicts between the development and operations teams. The problems further worsened by the occasional performance of activities such as planning, testing, integration, and releases. Many developing software development concepts reveal attempts to address these challenges. For instance, continuous integration is a practice that has emerged to reduce disconnects between development and IT operational deployments. In a comparable thread, the current emphasis on DevOps acknowledges that the integration between software development and its operational deployment needs to be a continuous whole. Problems involving the integration of software development and operations require positive synergy within DevOps teams. Team synergy brings about team effectiveness and performance as well as creating opportunities for innovation. The purpose of this study is to identify the factors that influence team synergy between the development and operations teams in a DevOps environment. The researcher conducted a case study at one of South Africa's leading information and communication technology services providers. Thirteen participants were interviewed to provide insight into the research questions. Interviews were conducted at the premises of the participating organization in Cape Town. The participants in the study preferred pseudonyms instead of their actual names to preserve anonymity. Interviews were transcribed and analysed using thematic analysis. During the analysis of the transcribed data, themes and categories were identified. The themes and categories that emerged from the data sources were aligned to the theoretical framework. The findings from this study describe enabling and inhibiting factors that influence the synergy between development and operations teams in a DevOps environment. Recognizing that DevOps teams face several challenges, the factors identified in this study provide insights into how organizations can influence the build and motivate their DevOps teams to achieve team synergy. The contribution to DevOps research is the application of a theoretical framework that suggests the importance of team social capital dimensions in the formation of team synergy. Based on its findings, this study recommends that further investigation and improvement on strategies to mitigate the factors that inhibit the dimensions of team social capital and prevent team synergy in a DevOps environment. The study also recommends a more detailed and practical demonstration to validate the value of the theoretical framework and continue to improve or extend it. This study revealed that DevOps teams operate in a complex and dynamic environment with many stakeholders and complex technical infrastructure. Based on this outcome, the study also suggests that future studies can take a different approach to create a different perspective on the synergy between DevOps teams by focusing on the behavior of the actors and complex problematic situations involving social activities.